Response to “Analysis of individual records of health services provision related to oral cancer in Colombia” (2016)
Dear EditorDr. Franklin EscobarIn response to the document written by Aristizabal and Roselli (1), referred to the section Letter to the Editor and related to the already published paper entitled “Epidemiological study of oral cancer in Colombia 1989-2008” (2), which I authored, I present the following considerations:Sirs Aristizabal and Roselli, I appreciate your interest in approaching a health issue as complex as oral cavity cancer, which has personal and social consequences, and to which I have devoted a lifetime of work from the most diverse points of view in relation to Oral and Maxillofacial Pathology. You are always welcome to provide constructive comments and critics. However, my recommendation, from a scientific and academic perspective, is to have the research findings assessed and analyzed by academic peers, experts in the field, to prevent that eventual doubtful products may be disclosed in prestigious journals.